2007
DOI: 10.2478/v10036-007-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Injuries in Freestyle Snowboarding

Abstract: Marek Strzała, Aleksander Tyka. Shaping of physical endurance and front crawl swimming technique indices in swimmers after half-year training period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Interestingly, we found in the majority of the cases that the injury was caused by an individual technical error (wrong timing, incorrect damping at take-off, losing control or catching the edge). This is supported by previous findings on freestyle snowboarders in national snowboard clubs 16. Furthermore, we identified that half of the technical errors were at take-off, resulting in a too-high-jump trajectory and a flat-landing beyond the intended landing zone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we found in the majority of the cases that the injury was caused by an individual technical error (wrong timing, incorrect damping at take-off, losing control or catching the edge). This is supported by previous findings on freestyle snowboarders in national snowboard clubs 16. Furthermore, we identified that half of the technical errors were at take-off, resulting in a too-high-jump trajectory and a flat-landing beyond the intended landing zone.…”
Section: Discussionsupporting
confidence: 90%
“…Jumping, which is an important feature of the SBX discipline, is thought to be another common cause of injuries for both recreational1114 and professional snowboarders 2 3 15. Zygmuntowicz and Czerwinski16 suggested that jumping-related injuries among freestyle riders in national snowboard clubs was a result of technical mistakes and rider errors, such as losing control, catching an edge and risk-taking.…”
Section: Introductionmentioning
confidence: 99%
“…Terrain parks contain metal features like rails and boxes to slide along, and striking a body part on the feature may result in injury 25. Chest/abdomen injuries were almost twice as likely in snowboarders than in skiers injured in terrain parks.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed examination of injury events in terrain parks could lead to design changes that decrease injury; for example, less difficult features for beginners, and marking the difficulty of terrain park features with the same ratings as traditional slopes 29. Formal instruction targeting young male snowboarders and focusing on technical jumping and landing skills may reduce injury 25. Lessons could be mandatory before access to difficult terrain parks is granted.…”
Section: Discussionmentioning
confidence: 99%
“…The main hazards of snowboard are high speed, hard-packed snow and limited visibility (Hasler et al, 2010). The most common causes of injuries are human mistakes (Bladin et al, 2004), usually of technical nature (Zygmuntowicz and Czerwiński, 2007). In freestyle snowboarding aerial disciplines, technical errors usually have strong impact on landing.…”
Section: Introductionmentioning
confidence: 99%